The H α Balmer line as an effective temperature criterion: I. Calibration using 1D model stellar atmospheres - Cayrel, R.; Van ’t Veer-Menneret, C.; Allard, N. F.; Stehlé, C. (Astronomy and astrophysics (Berlin), 2011)
Aims: We attempt to derive the true effective temperature of a star from the spectroscopic observation of its Hα Balmer line profile. Methods: The method is possible thanks to advances in two respects. First there have been progresses in the theoretical treatment of the broadening mechanisms of Hα. Second, there has been a rapid increase in the number of stars with an apparent diameter measured with an accuracy of the order of 1 percent, enabling us to obtain an accurate effective temperature Teff for a dozen of stars using the direct method by means of combining the apparent diameter and the bolometric flux. Results: For the eleven stars with an accurate effective temperature derived from their apparent angular diameter we determined the effective temperature of the Kurucz Atlas9 model that provides the best fit of the computed theoretical Hα profile (using the recent theoretical advances) with the corresponding observed profile, extracted from the S4N spectroscopic database. The two sets of effective temperatures have a significant offset, but are tightly correlated, with a correlation coefficient of 0.9976. The regression straight line of Teff(direct) versus Teff(Hα) enables us to reach the true effective temperature from the spectroscopic observation of the Hα profile, with an rms error of only 30 K. This provides a way of obtaining the true effective temperature of a reddened star. Conclusions: We succeeded in obtaining empirically the true stellar effective temperature from Hα profile using Kurucz's Atlas9 grid of 1D model atmospheres. Full understanding of the difference between Teff(direct) and Teff(Hα) would require a 3D approach, with radiative hydrodynamical models, which will be the subject of a future paper.